Assessing the Relationship of Patient Reported Outcome Measures With Functional Status in Dysferlinopathy: A Rasch Analysis Approach - Mayhew, Anna G.; James, Meredith K.; Moore, Ursula; Sutherland, Helen; Jacobs, Marni; Feng, Jia; Lowes, Linda Pax; Alfano, Lindsay N.; Muni Lofra, Robert; Rufibach, Laura E.; Rose, Kristy; Duong, Tina; et al. (Frontiers in Neurology, 2022)
Dysferlinopathy is a muscular dystrophy with a highly variable functional disease progression in which the relationship of function to some patient reported outcome measures (PROMs) has not been previously reported. This analysis aims to identify the suitability of PROMs and their association with motor performance. 204 patients with dysferlinopathy were identified in the Jain Foundation’s Clinical Outcome Study in Dysferlinopathy from 14 sites in 8 countries. All patients completed the following PROMs: Individualised Neuromuscular Quality of Life questionnaire (INQoL), International Physical Activity Questionnaire (IPAQ), and activity limitations for patients with upper and/or lower limb impairments (ACTIVLIM). In addition, non-ambulant patients completed the Egen Klassifikation Scale (EK). Assessments were conducted annually at baseline, year 1, 2, 3 and 4. Data were also collected on the North Star Assessment for Limb Girdle Type Muscular Dystrophies (NSAD) and Performance of Upper Limb (PUL) at these time points from year 2. Data were analysed using descriptive statistics and Rasch analysis was conducted on ACTIVLIM, EK, INQOL. For associations, graphs (NSAD with ACTIVLM, IPAQ and INQOL and EK with PUL) were generated from generalized estimating equations (GEE). The ACTIVLIM appeared robust psychometrically and was strongly associated with the NSAD total score - Pseudo R2 0.68. The INQOL performed less well and was poorly associated with the NSAD total score - Pseudo R2 0.18. EK scores were strongly associated with PUL - Pseudo R2 0.69. IPAQ was poorly associated with NSAD scores - Pseudo R2 0.09. This study showed that several of the chosen PROMs demonstrated change over time and a good association with functional outcomes. An alternative quality of life measure and method of collecting data on physical activity may need to be selected for assessing dysferlinopathy.